Role of yoga and physical activity in work-related musculoskeletal disorders among dentists - Koneru, Suneetha (J Int Soc Prev Community Dent, 2015)
BACKGROUND: Work-related musculoskeletal pain is one of the occupational hazards in dentists. Aims: To find the prevalence and severity of musculoskeletal pain in dentists, to compare musculoskeletal pain among dentists practicing yoga, those practicing physical activities, and those without any physical activity, and also to know the effects of sex, age, and workload on musculoskeletal pain. MATERIALS AND METHODS: A self-reporting work-related questionnaire and the Nordic questionnaire for analysis of musculoskeletal disorders were given to graduated dentists attending Indian dental conference in Mumbai, to know the musculoskeletal pain experienced in the last 12 months and feedback was obtained from 220 dentists. RESULTS: The prevalence of musculoskeletal pain in dentists was 34.5%. Prevalence of musculoskeletal pain was 10.5%, 21.7%, and 45.6% in dentists with regular yoga practice, other physical activity, and no physical activity, respectively. There was statistically significant difference in the prevalence of musculoskeletal pain among dentists who were practicing yoga when compared with those in no regular activity group. CONCLUSION: Within the limitations of the study, there was significant role of physical activity on the quality and quantity of work-related musculoskeletal disorders experienced by dentists. Yoga was found to be more effective than other modes of physical activities. More research is needed on musculoskeletal problems in dentists, with an emphasis on larger sample sizes and correlating other factors like age and sex of the dentists, duration of practice, years of practicing yoga, and working hours per week.